A multicenter, randomized, placebo-controlled, double-blind phase 3 trial with open-arm comparison indicates safety and efficacy of nephroprotective therapy with ramipril in children with Alport's syndrome - Gross, Oliver; Tönshoff, Burkhard; Weber, Lutz T.; Pape, Lars; Latta, Kay; Fehrenbach, Henry; Lange-Sperandio, Baerbel; Zappel, Hildegard; Hoyer, Peter; Staude, Hagen; König, Sabine; John, Ulrike; et al. (Kidney International, 2020)
Children with Alport syndrome develop renal failure early in life. Since the safety and efficacy of preemptive nephroprotective therapy are uncertain we conducted a randomized, placebo-controlled, double-blind trial in 14 German sites of pediatric patients with ramipril for three to six years plus six months follow-up to determine these parameters. Pretreated children and those whose parents refused randomization became an open-arm control, which were compared to prospective real-world data from untreated children. The co-primary endpoints were safety (adverse drug reactions) and efficacy (time to progression). Out of 66 oligosymptomatic children, 22 were randomized and 44 joined the open-arm comparison. Ramipril therapy showed no safety issues (total of 216.4 patient-years on ramipril; adverse event rate-ratio 1.00; 95% confidence interval 0.66-1.53). Although not significant, our results cautiously showed that ramipril therapy was effective: in the randomized arm, Ramipril decreased the risk of disease progression by almost half (hazard ratio 0.51 (0.12–2.20)), diminished the slope of albuminuria progression and the decline in glomerular filtration. In adjusted analysis, indications of efficacy were supported by prospective data from participants treated open label compared with untreated children, in whom ramipril again seemed to reduce progression by almost half (0.53 (0.22-1.29)). Incorporating these results into the randomized data by Bayesian evidence synthesis resulted in a more precise estimate of the hazard-ratio of 0.52 (0.19-1.39). Thus, our study shows the safety of early initiation of therapy and supports the hope to slow renal failure by many years, emphasizing the value of preemptive therapy. Hence, screening programs for glomerular hematuria in children and young adults could benefit from inclusion of genetic testing for Alport-related gene-variants.
CRIS-Team Scopus Importer:2020-04-24
Keywords: ACE inhibitors; albuminuria; Alport syndrome; chronic kidney disease; pediatric nephrology; renin-angiotensin system